Studies on the biochemistry of the Targeting domain of Lysostaphin - Antoniadou, Eleni (2004)
Lysostaphin from S. simulans was cloned in expression vector pET21a and expressed and purified in E .coli. A spot test and a broth dilution assay indicated that the minimum inhibitory concentration of lysostaphin required to kill EMRSA-16 was 40 nM. Lysostaphin consists of an endopeptidase and a trargeting domain the former of which codes for catalytic activity while the latter is responsible for substrate specificity. In order to find out whether the targeting domain of lysostaphin is an individually functional domain, it was cloned in vector pET21d and expressed in E. coli. The purified protein was assayed against EMRSA-16 in the presence of mature lysostaphin and it was found that the targeting domain alone can protect EMRSA-16 cells. This further indicated the potential of the targeting domain of lysostaphin to be used in future domainswapping studies with other proteins. Random PCR mutagenesis was used to identify putative active site residues in the C-terminal targeting domain of lysostaphin. One mutation was isolated, where a phenylalanine was replaced by a serine at position 172 of the mature protein. Sequence alignment with other lysostaphin homologues indicated the presence of three more conserved amino acids, two tyrosines at positions 203 and 226 and a tryptophan at position 214. Site-directed mutagenesis was employed to mutate all conserved residues to alanine and FI 72 to tyrosine to distinguish between important from unimportant sites. All six mutants (F172S, F172A, F172Y, Y203A, Y226A and W214A) were cloned and their proteins expressed and purified in E. coli. Their activity was assayed in an agar diffusion assay, a broth dilution assay, turbidimetrically and in a FRET assay. The results indicated that mutants F172S, F172Y, Y203A and Y226A remained bacteriolytic while mutants F172A and W214A had lost most of their activity, suggesting their significance in the activity of lysostaphin. Finally, a reversion experiment carried out with FI72A confirmed the importance of phenylalanine at position 172 of the mature protein.